1987
DOI: 10.1111/j.1399-0004.1987.tb02835.x
|View full text |Cite
|
Sign up to set email alerts
|

The Brachmann‐de Lange syndrome in two siblings of normal parents

Abstract: In this report we describe two male siblings with typical Brachmann‐de Lange syndrome. Both presented a severe form of this MCA syndrome, and died at the age of 3 months and 3 weeks, respectively. Family history was completely negative, parents were normal, and prometaphase chromosome studies failed to reveal a chromosomal basis for this unique malformation syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 9 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…In this respect recurrence in sibs could be explained by germ cell mosaicism, as is well known in other autosomal dominant conditions, e.g. achondroplasia (Frijns et al 1983).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…In this respect recurrence in sibs could be explained by germ cell mosaicism, as is well known in other autosomal dominant conditions, e.g. achondroplasia (Frijns et al 1983).…”
Section: Discussionmentioning
confidence: 82%
“…Most cases occur sporadically in an otherwise normal family, but familial occurrence of BDLS has repeatedly been reported. At least three instances of recurrence in sibs with apparently healthy parents have been described, suggesting autosomal recessive inheritance (Lieber et al 1973, Frijns et al 1987, Naguib et al 1987.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in the authors' database, germline mosaicism ranges from a conservative 3.4% (12 families out of 351 with confirmed proband mutations) up to 5.4% (19 out of 351, including seven families with unknown mutations in the affected probands) [Slavin et al, ]. In keeping with these findings, Slavin et al [] state that the previous reported recurrence rate of 1.5% due to germline mosaicism, based on “various reported cases of apparently unaffected parents who had two or more children affected,” could constitute an under‐representation of the real situation [Beratis et al, ; Lieber et al, ; Naguib et al, ; Fryns et al, ; Jackson et al, ; Krajewska‐Walasek et al, ].…”
Section: To the Editormentioning
confidence: 99%